Administrative reforms: no panacea for good governance - Agarwal, U.C. (1998)
The administrative machinery in some states is directly or indirectly coming under the control and direction of undesirable leadership. Unless these developments are curbed soon, administrative chaos may not be far away. Some radical electoral and political reforms are called for. Minor surface changes by way of administrative reforms may not be of much help now. Our parliamentary democracy unfortunately is proving to be too costly to the country, socially, politically, economically and of course administratively. The need of the hour therefore is to reform the political system first. Mere administrative reforms may not be of much use in the prevailing political climate as no recommendation however sound is likely to be accepted or faithfully implemented in the present political situation. - Reproduced
Keywords: Administrative reform